Development of an IoT-based Augmentative and Alternative Communication (AAC) for stroke patients using QFD - Anto , Fitrah Japunk Lucky; Widiyanti, Syafira; Prayogi , Agung; Ismianti, Ismianti; Prian Tahalea, Sylvert; Wahyu Adventri Wibowo , Astrid; Amalia Permadi , Vynska (OPSI, 2025)
Stroke is one of the leading causes of death globally, after heart disease and cancer. It often results in brain damage that impairs the function of certain body parts, including the ability to communicate. Communication disorders in stroke patients can severely impact mental health and quality of life, with studies showing that 53% of affected individuals experience depression. This study aims to design and develop an assistive communication tool tailored to the needs of stroke patients. The Quality Function Deployment (QFD) method was employed to ensure that user requirements are thoroughly addressed in the design process. Data were collected through observations and interviews with nurses and families of stroke patients. The House of Quality (HoQ) analysis revealed three main priorities for development: an integrated information system, blink-based control, and a feature to detect patient needs. The resulting solution is IISAAC (IoT-based Integrated System with Augmentative and Alternative Communication), a communication system that uses eye blink signals detected via an EOG sensor. These signals are converted into specific messages and sent directly to the nurse’s WhatsApp application. IISAAC enables more effective communication between patients, caregivers, and medical staff, helping to address the communication barriers commonly experienced by stroke survivors.